2022
DOI: 10.1007/s40123-022-00633-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility and Safety of Scleral Collagen Cross-Linking by Riboflavin and Ultraviolet A in Pathological Myopia Blindness: A Pilot Study

Abstract: Introduction To investigate the feasibility and safety of scleral ultraviolet A (UVA) cross-linking (scleral CXL) on pathologically blindness. Methods This was a prospective, observational clinical study. Five patients with monocular blindness due to pathological myopic maculopathy were enrolled. Eyes with best corrected visual acuity (BCVA) under 0.05 were defined as experimental eyes. The fellow eyes were defined as control eyes. Patients first underwent posterior scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…High myopic eyeballs expanded globally, especially in axial length (AL) 2 . With the AL elongation, high myopia can cause many ocular complications in posterior segment, such as retinal thinning, degeneration, myopic maculopathy, detachment, posterior staphyloma, choroid neovascularization, and eventually lead to non-reversible visual impairment 3 . Previous literature had suggested that eyeball radius increase in high myopia eyes leaded to the retinal blood circulation reduction.…”
Section: Introductionmentioning
confidence: 99%
“…High myopic eyeballs expanded globally, especially in axial length (AL) 2 . With the AL elongation, high myopia can cause many ocular complications in posterior segment, such as retinal thinning, degeneration, myopic maculopathy, detachment, posterior staphyloma, choroid neovascularization, and eventually lead to non-reversible visual impairment 3 . Previous literature had suggested that eyeball radius increase in high myopia eyes leaded to the retinal blood circulation reduction.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 By taking advantage of the tissue targeting of cross-linking, 8 it is possible to treat the equatorial sclera. 9 If the photosensitizer and the irradiated light can reach the posterior sclera (e.g. using flexible optical waveguides 10 or LED probes 11 ), photo-crosslinking may be a viable technique to strengthen the sclera and arrest myopia.…”
mentioning
confidence: 99%